Numerical simulation analysis of settlement for super-large diameter shield tunneling undercrossing high-speed railway subgrade - LOU Hongjun; SU Dong; LIN Xingtao; WANG Xuetao; SONG Ming (Shenzhen Daxue xuebao. Ligong ban)
To explore the settlement characteristics of intercity railway subgrade induced by super-large diameter shield tunneling, taking the Lianghu Tunnel Project in Wuhan as an example, we establish a three-dimensional refined numerical model of the railway subgrade-soil-tunnel by using the finite element software Plaxis. The influences of the ground loss ratio, tunnel face support pressure, and grouting pressure at the shield tail on the settlement law of the intercity railway subgrade above the tunnel are investigated during shield tunneling. The simulation results show that during the process of shield penetration into the composite strata, the surface of the ballast layer of the high speed railroad foundation experiences varying degrees of settlement in the direction of shield tunnel excavation. When the ground loss ratio caused by shield tunneling increases from 1.0% to 1.6%, the maximum settlement of the railway subgrade increases by about 20.4% from 18.86 mm to 22.71 mm. When the tunnel face support force is 0.7 to 1.4 times the lateral static earth pressure of the tunnel vault, the difference in the deformation of the railway subgrade caused by shield tunneling under different tunnel face support pressures is minor (less than 0.67 mm). The grouting pressure obviously influences the settlement of the railway subgrade. As the grouting pressure increases, the settlement of the railway subgrade decreases significantly. When the grouting pressure of the tunnel crown increases to 3 times the lateral static earth pressure of the crown (648 kPa) or more, the maximum differential settlement along the railway subgrade does not exceed the specification requirement (≤ 5 mm/10 m). The results of the study can provide references for setting excavation parameters for the super-large-diameter shield undercrossing high-speed railway subgrade.